Origin in the estimation of blood money (diyyah) - Muhammad Husni, Ahmad; Muhammad Husni, Amin Bin (Zes Rokman Resources (2131022-P), 2022)
The issue of blood money (diyyah) has toppled the concern of both jurists and the judiciary because of its great importance in people’s daily lives. Therefore, the aim of the study is to meet the urgent need for the study of blood money (diyyah) and the explanation of its practical applications in this day for its important role for protecting bloodshed, crime prevention and its impact on the stability of Muslims societies. And here lies the importance of the research to know the origin of blood money (diyyah) – in the estimation of blood money (diyyah)-, and also to achieve the amount of blood money (diyyah) because its aim is to search by extrapolating the views of the four Schools of thought in terms of ruling on blood money (diyyah) and to analyse and discuss the positions of agreement and disagreement among them; and also to look at the views of the contemporary jurists to choose the provisions that fit the developments of the current era. So, the subject of my research is divided into several parts in order to give a clear picture of blood money (diyyah). And through the research we found some results, including: estimating blood money (diyyah) in the current era on the basis of estimating the value of a camel at the time of the Prophet (saw) is the first section, and this is the process of our research, while other sections will come later, to determine the principle of Aqilah on the basis of cooperation is the second section, and the permissibility of the Islamic, cooperative and social insurance companies to represent Aqilah in the payment of blood money (diyyah) is the third section, and the equality of women to men in blood money (diyyah) related to soul and below is the final section.